2008
DOI: 10.1111/j.1939-3938.2006.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital Findings of Women After Consensual and Nonconsensual Intercourse

Abstract: After a sexual assault, forensic nurses, nurse practitioners, and physicians are called on to collect evidence, document any genital injuries, and testify about the significance of injuries. Recently, the scientific rigor of the research has been challenged in the courts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 19 publications
7
70
2
2
Order By: Relevance
“…In contrast to other work, in a recent study the investigators reported that 30.4% of consensual participants (n = 46) and a surprisingly low 32.1% of nonconsensual participants (n = 56) had genital injury (Anderson, McClain, & Riviello, 2006). Although the study had significant methodological problems such as small sample size; heterogeneity of groups with regard to age, history, and time to examination; and lack of adequate matching procedures, the study raises interesting questions about the low injury prevalence in the consensual population reported previously.…”
Section: Is Injury Prevalence Following Consensual Sexual Intercoursecontrasting
confidence: 64%
“…In contrast to other work, in a recent study the investigators reported that 30.4% of consensual participants (n = 46) and a surprisingly low 32.1% of nonconsensual participants (n = 56) had genital injury (Anderson, McClain, & Riviello, 2006). Although the study had significant methodological problems such as small sample size; heterogeneity of groups with regard to age, history, and time to examination; and lack of adequate matching procedures, the study raises interesting questions about the low injury prevalence in the consensual population reported previously.…”
Section: Is Injury Prevalence Following Consensual Sexual Intercoursecontrasting
confidence: 64%
“…The lesions were predominantly located in the posterior forchette [2,6,10] in studies that mentioned site. Two of the four studies that mentioned type had lacerations as the predominant lesion [2,7], whereas the other two found bruising to be predominant [6,10]. Three studies had information regarding number of lesions.…”
Section: The Nature Of Lesionsmentioning
confidence: 96%
“…A review of the literature identifies seven studies of lesions seen after consensual sexual intercourse among adults, four recent [2,5,6,7] and three older studies [8][9][10]. One study describes lesions seen after consensual sexual intercourse in adolescents aged 13-17 years [11].…”
Section: Genital Lesions Sustained During Consensual Sexual Intercoursementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation, abrasions, and injury can result from both forced and consensual sex, 30,31 although most studies associate higher rates (up to three times higher) of injury with sexual assault. [32][33][34] Rates of reported injury in cases of forced sex vary immensely, with studies estimating between 32% 30 and 94%.…”
Section: Research Prioritiesmentioning
confidence: 99%